Chemical and Biological Diversity of the Leaf and Rhizome Volatiles of Acorus calamus L. from Turkey. Issue 3 (4th May 2017) - Süzgeç-Selçuk, Sevda; Özek, Gülmira; Meriçli, Ali Hikmet; Baser, Kemal Hüsnü Can; Haliloglu, Yesim; Özek, Temel
Abstract: Two different isolation techniques, conventional hydrodistillation (HD) and micro-steam distillation-solid-phase microextraction (MSD-SPME), have been used to analyze the volatile constituents from the leaves and rhizomes of Acorus calamus L. by gas chromatography (GC-FID) and gas chromatography coupled to mass spectrometry (GC-MS). In all the samples studied, phenylpropanoids (16.9-35.3 %) predominated by β-asarone (15.3-16.3 % in rhizomes, 23.4-31.7 % in leaves) were the main constituent. In addition to phenylpropanoids, the acorane type sesquiterpene acorenone B (7.4-16.4 %) and elemene-type sesquiterpenes, epi-isoshyobunone (3.3-7.3 %) and shyobunone (1.5-4.6 %) were detected among the major volatile constituents in the rhizomes. The monoterpenes were represented by camphor (7.5-13.9 %) and camphene (6.1-7.7 %). In the leaf, myrcene (0.3-7.1 %), limonene (1.0-5.6 %), ( Z )-β-ocimene (2.9-6.1 %) were among the major constituents. Qualitative difference of the volatiles composition in the rhizomes and leaves are discussed as well as of the volatiles obtained by HD and MSD-SPME techniques are discussed. Biological activity tests resulted in moderate anti-acetylcholinesterase effect and significant cupric reducing antioxidant potential of the leaf oil, while the rhizome oil demonstrated relatively lower effects.